2012
DOI: 10.1021/om2010996
|View full text |Cite
|
Sign up to set email alerts
|

Halostibines SbMeX2 and SbMe2X: Lewis Acids or Lewis Bases?

Abstract: Alkylhalostibines have been shown to behave either as Lewis acids toward appropriate neutral ligands or as Lewis bases to low-valent metal fragments. The boundaries of their Lewis acid and Lewis base behavior have been determined, and the structural and spectroscopic consequences of the different behaviors probed. [SbMeX 2 (L−L)] (L−L = 2,2′-bipyridyl, 1,10-phenanthroline) and [SbMeX 2 (L) 2 ] (L = OPMe 3 , OPPh 3 ) are five-coordinate, distorted squarepyramidal monomers with the Me group axial, with the bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 64 publications
0
53
1
Order By: Relevance
“…The products are relatively stable in air and the BiÀMe units less fragile than in the parent halobismuthines. The same bases bring about disproportionation in BiMe 2 X, the reaction being driven by complexation of the BiMeX 2 produced; similar behaviour occurs with SbMe 2 X and diimines [14]. The group 6 metal carbonyl reagents [M(CO) 5 (thf)] (M ¼ Cr or W) also promote disproportionation of BiMe 2 Br, in this case the BiMe 3 that is produced complexes with the metal centre to form [M(CO) 5 (BiMe 3 )].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The products are relatively stable in air and the BiÀMe units less fragile than in the parent halobismuthines. The same bases bring about disproportionation in BiMe 2 X, the reaction being driven by complexation of the BiMeX 2 produced; similar behaviour occurs with SbMe 2 X and diimines [14]. The group 6 metal carbonyl reagents [M(CO) 5 (thf)] (M ¼ Cr or W) also promote disproportionation of BiMe 2 Br, in this case the BiMe 3 that is produced complexes with the metal centre to form [M(CO) 5 (BiMe 3 )].…”
Section: Discussionmentioning
confidence: 77%
“…The group 6 metal carbonyl reagents [M(CO) 5 (thf)] (M ¼ Cr or W) also promote disproportionation of BiMe 2 Br, in this case the BiMe 3 that is produced complexes with the metal centre to form [M(CO) 5 (BiMe 3 )]. In contrast, SbMe 2 Br functions as a Lewis base towards the same metal carbonyls forming stable [M(CO) 5 (SbMe 2 Br)] adducts [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently made an effort to draw the boundaries of these behaviours, 28 and have found that the mixed alkylhalostibines prove a fertile ground for unusual coordination chemistry in which both behaviours are often observed …”
Section: Dual Donor and Acceptor Behaviour Of Halostibines And Halobimentioning
confidence: 99%